Urgensi Penyuluhan Berbasis Wawasan Kebangsaan Terhadap Remaja Masjid - Juwono, Hendro (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2019)
In adolescence is needed coaching to solve and overcome problems faced. A person's personality must be fostered through special education to fit the values in society and culture, especially the youth community. Teenagers also have many life problems, from personal problems, family, friends, and even other social problems. One of the urgent coaching in the era of globalization for adolescents is to conduct counseling based on national insight as a form of deradicalization. National-based counseling aims to increase and strengthen understanding of how to become good citizens. The research method in this article uses a qualitative approach to the type of literature. Qualitative research is expected to be able to facilitate and bridge.